Maternal Distress in Disclosing a Nonlethal Fetal Anomaly Diagnosis to Family and Friends. Issue 4 (July 2022) - Tucker, Janet Adams; Christian, Becky J.
Abstract: Purpose: To describe experiences of women disclosing a nonlethal fetal anomaly diagnosis to family and friends from initial prenatal diagnosis through postpartum. Study Design and Methods: A descriptive, qualitative approach was used to explore women's perceptions of nonlethal fetal anomaly diagnosis in a high-risk obstetric clinic. In-depth interviews were conducted with 10 pregnant women, followed by postpartum interviews with 8 women. Data were analyzed using thematic analysis. Results: Analysis of semistructured interviews revealed an overarching theme, Pregnancy Forever Changed, which captured the experience when expectant women first heard the news about their fetus. Prenatal themes were News of a Diagnosis, No Going Back; A Mother's Response: Managing Information; and Words from Others Matter . Women's struggles continued into postpartum, The Journey Continues: Echoing Past Concerns; and Not the Journey We Planned . Clinical Implications: Women with a nonlethal fetal anomaly diagnosis experienced distress and stigma about disclosure of the diagnosis to others. Distress with disclosure continued throughout the pregnancy and extended into postpartum. Women described negative responses from others and ongoing management of information as stressful and painful. Clinicians are aware disclosing a lethal diagnosis is distressing for women but may not understand the experience of women with a nonlethal diagnosis. An appreciation of women's distress on disclosure of nonlethal fetal anomaly diagnoses can guide practice for maternity, neonatal, and pediatric nurses providing interventions that include information and anticipatory guidance. Abstract : Approximately 3% of pregnant women will learn of a fetal anomaly during their pregnancy. The anomaly could be diagnosed as lethal or non-lethal. In this study, women who received a diagnosis of non-lethal fetal anomaly share their experiences with disclosing this information with their family and friends. Most women describe the experience as very stressful and appreciated information and support from their health care team during pregnancy and postpartum.